Numerical analysis of nonlinear behavior of steel-concrete composite structures - Í.J.M. LEMES; A.R.D. SILVA; R.A.M. SILVEIRA; P.A.S. ROCHA (Revista IBRACON de Estruturas e Materiais)
Abstract This paper presents the development of an effective numerical formulation for the analysis of steel-concrete composite structures considering geometric and materials nonlinear effects. Thus, a methodology based on Refined Plastic Hinge Method (RPHM) was developed and the stiffness parameters were obtained by homogenization of cross-section. The evaluation of structural elements strength is done through the Strain Compatibility Method (SCM). The Newton-Raphson Method with path-following strategies is adopted to solve nonlinear global and local (in cross-section level) equations. The results are compared with experimental and numerical database presents in literature and a good accuracy is observed in composite cross sections, composite columns, and composite portal frames.